Relationship between biochemical analytes and milk fat/protein in Holstein cows - Prado, Omar R.; Morales, Jesús B.; Molina, Jaime O.; García, Luis M.; Macedo, Rafael B.; Hernández, Juan R.; García, Arturo C. (Austral Journal of Veterinary Sciences, 2019)
The aim of this study was to assess the relationship between biochemical analytes and milk fat/protein in high-yield (DIM: 42 ± 10 d postpartum) and low-yield (DIM: 91 ± 11 d postpartum) Holstein cows. Stepwise regression analysis was used to evaluate the relationships of biochemical analytes with the fat and protein content of the milk from 126 Holstein cows belonging to nine intensive housed dairy farms. The comparison between the two groups showed differences (P<0.05) in the milk yield, milk fat and milk fat/protein ratio, with the higher values in high-yield cows. The correlations between milk fat, milk protein, milk fat/protein ratio and biochemical analytes concentrations, were assessed within each group. Milk fat level was positively correlated to cholesterol, triglycerides, p-hydroxybutyrate and albumin in high-yield cows. Milk protein level was positively correlated to urea, and negatively correlated to sodium ion, potassium ion and chlorine ion in high-yield cows. A virtually linear dependence has also been found between milk fat and triglycerides, between milk protein and urea, and between milk fat/protein ratio and cholesterol, and triglycerides in low-yield cows. The metabolic profiles provide a practical tool, to present an insight into the underlying physiological mechanisms of lactation, and the identification of relationships between key analytes and components of milk, such as protein and fat content.